Chronology of Land Planning, Conflict and Intractability: The Case of East Forest Reserve Bogota - Rojas-Pinilla, Humberto (Universidad del Rosario, 2017)
The main conflict intractability features are long duration, pervasiveness and the systematic resistance to conflict resolution attempts, as well as the state role and disputes over fundamental needs, seen as strong “cultural and structural issues”. This article focuses in the ways in which, through time, it has been constructed a “Habitus” prone to conflict intractability as a consequence of temporary and structural elements related to particularly problematic land planning and population management practices. The article also points out the complex and entangled relations between the features of intractability with the conflict generated by the urbanization of holdingsaffected by a National Forest Reserve declaration in Bogotá.